Entendre les mouches voler - Sarah Benabou; David Picherit (Ateliers d'Anthropologie)
This article presents the issues and the heuristic character of a sound-based approach to a political anthropology of the environment. Based on an experimental interdisciplinary project bringing together anthropologists, ecologists, sound artists and museologists, it examines the ways in which attention to sound makes it possible to understand the complex dynamics of the Valparai plateau (South India), where a plantation regime is entangled with a forest conservation regime. Using group sound-walks as a preferred study method, this approach immediately raises the question of the “positionality” from which we listen to the world, and thus opens the door to a political-environmental mapping of the territory that is attentive to the circulation of humans, animals and sound. Nevertheless, this understanding is only possible on condition of adopting a deliberately ethnographic position, that is to say one that gives attention to inclusive sound landscapes whose interpretation rests on a perpetual to-and-fro between the group’s epistemological intuitions and sensory observations. This is how it is possible to hear the multi-layered sounds of power—and of that which resists it.